Inovasi Kerajinan Ecoprint Berbasis Lingkungan: Workshop Kreativitas untuk Pemberdayaan Perempuan Desa Padamenak - Rezeki, Ingrid Multi; Meidelina, Alya Verda; Rahmah, Jasmine Aulia; Alfiyan, Mohammad Rosid; Yani, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Padamenak Village, located in the Jalaksana District, covers an area of 33.130 hectares and is situated at an altitude of 500-600 meters above sea level, with a tropical climate. It consists of 2 RW (neighborhood units) and 6 RT (community units), divided into two hamlets: Dusun Padaasih and Dusun Padamulya. One of the initiatives for empowering women is the ecoprint craft training, which utilizes natural materials without harmful chemicals. Through this workshop, women are trained to create fabrics, bags, and accessories based on ecoprint, enhancing their skills and economic independence. This program not only enriches the art of handicrafts but also supports a sustainable creative economy.